Double Peaks of the Solar Cycle: An Explanation from a Dynamo Model - Karak, B.B.; Mandal, S.; Banerjee, D. (Institute of Physics Publishing, 2018)
One peculiar feature of the solar cycle that is yet to be understood properly is the frequent occurrence of double peaks (also known as the Gnevyshev peaks). The double peaks, and also multiple peaks and spikes, are often observed in any phase of the cycle. We propose that these peaks and spikes are generated due to fluctuations in the Babcock-Leighton process (the poloidal field generation from tilted bipolar magnetic regions). When the polar field develops, large negative fluctuations in the Babcock-Leighton process can reduce the net polar field abruptly. As these fluctuations in the polar field are propagated to the new toroidal field, these can promote double peaks in the next solar cycle. When fluctuations in the polar field occur outside the solar maximum, we observe their effects as spikes or dips in the following sunspot cycle. Using an axisymmetric Babcock-Leighton dynamo model, we first demonstrate this idea. Later, we perform a long simulation by including random scatter in the poloidal field generation process and successfully reproduce the double-peaked solar cycles. These results are robust under reasonable changes in the model parameters, as long as the diffusivity is not too much larger than 1012 cm2 s-1. Finally, we analyze the observed polar field data to show a close connection between the short-term fluctuations in the polar field and the double peaks/spikes in the next cycle. Thereby, this supports our theoretical idea that the fluctuations in the Babcock-Leighton process can be responsible for the double peaks/spikes in the observed solar cycle. © 2018. The American Astronomical Society. All rights reserved..
Keywords: dynamo – magnetohydrodynamics (MHD); Sun: activity; Sun: interior; Sun: magnetic fields; sunspots